2005
DOI: 10.1103/physreve.72.051706
|View full text |Cite
|
Sign up to set email alerts
|

Orientational instabilities in nematic liquid crystals with weak anchoring under combined action of steady flow and external fields

Abstract: We study the homogeneous and the spatially periodic instabilities in a nematic liquid crystal layer subjected to steady plane Couette or Poiseuille flow. The initial director orientation is perpendicular to the flow plane. Weak anchoring at the confining plates and the influence of the external electric and/or magnetic field are taken into account. Approximate expressions for the critical shear rate are presented and compared with semianalytical solutions in case of Couette flow and numerical solutions of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Under pressure-driven flow, a distinctly different, often symmetric about the cell midplane, velocity distribution is observed [15] (see Fig. 2).…”
mentioning
confidence: 94%
“…Under pressure-driven flow, a distinctly different, often symmetric about the cell midplane, velocity distribution is observed [15] (see Fig. 2).…”
mentioning
confidence: 94%
“…6,7 Such shear flow experiments regularly involve the flowing of a liquid crystal sample between two glass plates by way of dragging one plate relative to the other at a constant velocity, producing a linear velocity distribution across the depth of the cell. In the Poiseuille flow study presented here, a distinctly different flow distribution is observed ͑particularly at low rates͒, 8 a parabolic distribution of flow speeds symmetrical about d / 2 ͓see Fig. 1͑a͔͒, characteristic of any classical pressure gradient flow regime.…”
mentioning
confidence: 99%
“…The theoretical description taking into account weak anchoring was developed in the past decade [69,[77][78][79][80][81][82]. It is obvious that the effects of weak anchoring (see Chapter 5) have to modify both static and dynamic behavior of liquid crystals as in the case of electric fields.…”
Section: Shear Flows At Weak Anchoringmentioning
confidence: 99%
“…Recently, the influence of weak anchoring on nonlinear phenomena induced by shear flows in nematic liquid crystals was considered in some publications [80][81][82]. The developed theoretical description is restricted to the simplest type of instabilities arising under steady flows (plane Couette or Poiseuille flows) in the samples with the initial planar orientation normal to the flow plane (see Sections 3.3.1 and 3.3.2).…”
Section: Hydrodynamic Instabilities At Weak Anchoringmentioning
confidence: 99%
See 1 more Smart Citation